HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DENGAN PERILAKU MASYARAKAT DALAM PEMILAHAN SAMPAH RUMAH TANGGA DI DESA GUNAKSA KLUNGKUNG TAHUN 2022 - Kadek Cristina; Mochammad Choirul Hadi; I Made Bulda Mahayana; Iin Indayani (Poltekkes Kemenkes Denpasar, 2023)
Abstract : Gunaksa Village is one of the villages in Dawan Sub-district where some people donot sort the waste they collect, so that at TOSS Werdhi Guna, the officers sort it again. Purpose of research this that is for know level knowledge and attitude with behavior public in sorting rubbish House stairs in the village Use . Type This research is a cross sectional study. This study used 58 samples. Data collection was carried out using a one-way questionnaire and sheet observation . Results from study this is known that level knowledge with behavior public in sorting rubbish showed by p-value0.000 where results this 0.05 = 0.523 and attitudes with people's behavior in sorting rubbish House ladder showed by p-value 0.000 where results This0.05 = 0.587 which is the level of the moderate relationship. So it can be concluded that there is a relationship between knowledge and attitudes with people's behavior in sorting rubbish households in Gunaksa Village. It is hoped that the Puskesmas in the working area of Gunaksa Village and community leaders will provide counseling about what impacts will be caused by not carrying out waste sorting.